INTENSIFICATION OF BIODIESEL PRODUCTION FROM JATROPHA ON IN-SITU TRANSESTERIFICATION - ISMAIL, ROSFAIZUL (Universiti Teknologi PETRONAS, 2009)
Process intensification is defined as improvement of process mainly reaction by any possible means to increase the overall productivity. This work presents the study of intensification methods that can be applied to biodiesel synthesis using Jatropha seed via in-situ transesterification. Jatropha is selectedas the source of the biodiesel due to it inedible properties and high oil contents. The small percentage of acid value in the seeds only required single step transesterification process. The Jatropha seeds will be extracted chemically (in situ) to preserve the quality and getting high yield on instant with transesterification process. Transesterification is a method to reduce the oils viscosity and the best practiced in biodiesel production than other methods. The process can be catalyzed either by acid, alkalis or enzyme. The utilization of biodiesel in replacing the existing diesel from fossil resources, contributes in solving many environment problems. For process intensification, the effect of ultrasonic will be investigated. The method claims to increases the chemical reaction speed by cavitations effect giving sufficient activation energy for the transesterification process. Besides that, the investigation on the effect of heterogeneous catalyst towards the production efficiency will also be performed. All the research and findings obtained will be applied to find the optimum parameters for biodiesel production in lab scale.